Pembuatan Perangkat dan Aplikasi Sistem Vending Machine Berbasis Arduino Leonardo dan Android - Sulisthio, Andrew Kurniawan; Yulia, Yulia; Khoswanto, Handry (Jurnal Infra, 2016)
The concept of Internet of Things (IoT) where an inanimate object connects to internet network, made this technology concept very popular nowadays. Supported by famous technologies such as Arduino and Android, which makes combination of these three things able to give added benefits to the users. Application of these three, in the scope of vending machine is very appropriate given that there is a big market opportunity for vending machine especially in Indonesia. With those in mind, an idea to make an integrated vending system that consist of vending machines where its management and purchasing application resides within an Android application is created. This system, intended to give users such as managerials and customers a benefits and ease of use.Vending system is designed as is using Android programming, Arduino programming and server configuration so that it can meet the needs of a system that integrated on to another in the scope of IOT concept. The testing process of this system is managed through the functions of product, user, vending machine and promo data management so that the vending machine can runs as desired.The outcome of the combination of this IOT concept, Arduino Android technology and MySQL server is an interconnected system through internet network that consist of 3 parts. The first part is a server which acts like an intermediary medium between the other 2 parts. The second part is the physical vending machine that based on the Arduino technology. The last part is the management and purchasing application that based on the Android mobile technology.